Analisa Potensi Titik Reklame di Kota Batam - Ely Kartikaningdyah (Politeknik Negeri Batam, 2009)
Batam as one strategic area of industrial development in Indonesia and has a high potential as a medium to commercialize a company or certain products. This is certainly great potential for city government to increase the maximum extent possible Batam original income (PAD) of this advertisement sector. In the current era of autonomy, local governments have the authority to seek in the broader region income optimization. One source of local revenues of the most potential for increased tax revenues and user charges are billboards. The rapid development of information technology makes the business, users of this information technology services to introduce products utilizing billboards, logos and service from the company to the consumers and the general public. Fitting logos, products and services in public places in the size and design in such a way, indirectly will attract interest and attention for the products, services, or logos of any company or institution. Fundamental changes should be made by policy makers in giving permission for laying and designing billboards and buildings that violate field function and retention of green open space. Especially for billboards, shape and placement of the board should consider several things, including spatial function, width of road, visibility, height of buildings, areas and buildings can be maintained to safeguard the privacy of urban space, it is expected the city government can set rules permit the determination of the installation, billboard layout arrangement by establishing a strategic point which does not interfere with the spatial area of the city. Structuring consider several aspects: Legal Aspects, Strategic Value Aspects, Social Aspects, Economics and Environment. The results showed income from tax in Batam city billboards can provide greater potential if the arrangement of the layout stage billboard locations governed better by enhancing the strategic value of an area / zone billboard stage. The analysis is based on consideration of the road grade classification (arterial, collector and local), the density of usefulness / bustle of an area or public facility within or outside the municipal area (airport, seaport, bridge crossings and bus stops), crossing the road each area / zone will have a sale value of different points billboard stage with zone / area other billboard, which will be increased in accordance with the development of Batam as a free trade zone. Results of economic analysis, financial, strategic value of the potential of a region that can become a taxable sale value of the advertisement should be reassessed with local regulations and the determination is based on points and setting the stage billboard billboard strategic value. Results of social analysis of environmental, Batam is potential for the development of the business world so that means the installation of billboards will still be many diminiati by the stockholder. The SWOT analysis, there are opportunities that will be obtained to increase the potential of local tax revenue through the advertisements of some areas not fully utilized.